TATA KELOLA PERUSAHAAN DALAM ERA TEKNOLOGI DISRUPTIF DI INDUSTRI INDONESIA - Yohan Purnawan; Hendri Mayanta; Muhammad Rijal Panjaitan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study examines corporate governance in the face of disruptive technologies in Indonesia’s industries, with an emphasis on organizations (particularly in e-commerce) undergoing digital transformation. The study highlights that digital transformation is not merely a technology investment, but a strategic necessity that requires alignment among business strategy, corporate governance practices, and human resource adaptability. Disruptive technologies such as blockchain, artificial intelligence (AI), and Big Data can enhance transparency and operational efficiency as well as strengthen decision-making, but they also introduce new challenges, including cyber threats, difficulties in integrating legacy systems, data privacy and security issues, and evolving regulatory constraints. The research employs a literature review approach, thematic analysis, and case-study insights within Indonesian company contexts. The findings indicate that successful digital transformation is strongly influenced by the ability of governance to adapt, the presence of effective digital leadership, and the implementation of adaptive governance to anticipate and manage disruptive risks. The study also shows that transformation failures are often caused by legacy system issues, skill gaps in digital capabilities, inadequate budgeting and ROI risk management, cybersecurity threats, and weak internal communication. The recommendations stress the importance of integrating traditional governance mechanisms with adaptive/agile approaches, including the use of IT governance frameworks such as COBIT to improve governance maturity and oversight effectiveness.